2024
DOI: 10.24084/repqj07.319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Environmental and Life Cycle Impact of a Switched Reluctance Motor Drive and Inverter-Fed Induction Motor Drives

Abstract: Abstract. This paper compares the environmental and life cycle impact of one switched reluctance motor (SRM) drive and two inverter-fed induction motor (IM) drives. The study was carried out according to the Directive on the Ecodesign of Energy-Using Products (EuP 2005/32/EC) and following the Methodology for the Ecodesign of Energy-Using Products (MEEUP). The following base-case models were used: an IM (Eff3), an IM (Eff1) and an 8/6 SRM. All of these base-case models are rated at 1.5 kW of output power and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…This paper deals about the environmental impact and life cycle analysis of one SRM drive and two IM drives. It extends previous research conducted by the authors on the environmental impact of SRM drives, and on comparison of SRM and IM drives in environmental terms [10,11]. It contains more critical reasoning regarding the bases of comparison between the two drive types, and considers EC Regulation 640/2009.…”
Section: Introductionsupporting
confidence: 53%
“…This paper deals about the environmental impact and life cycle analysis of one SRM drive and two IM drives. It extends previous research conducted by the authors on the environmental impact of SRM drives, and on comparison of SRM and IM drives in environmental terms [10,11]. It contains more critical reasoning regarding the bases of comparison between the two drive types, and considers EC Regulation 640/2009.…”
Section: Introductionsupporting
confidence: 53%
“…3 (Andrada et al 2009;Jardot et al 2010), whereas those for the proposed design were obtained using the procedure indicated in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to transportation field, the electric motor environmental impact, focusing also on the rare-earth magnet is evaluated recurrently in literature [7], [8], [9], [10], [11], through comparison of synchronous reluctance machine (synRM), permanent magnet-assisted synchronous reluctance machine (PM-assisted RM), PMSM adopting different magnet materials, induction motors (IM) and externally excited synchronous machine (EEsynM). Referring to SRMs, only one Life Cycle Assessment (LCA) study [12] was found in literature and not referred to transportation field, with specific reference to passenger car. Indeed, the magnet free solution is compared with two IMs representative of the low power range (1.5kW).…”
Section: Introductionmentioning
confidence: 99%